DIETARY UTILIZATION OF SELECTED VEGETABLE PROTEINS BY MULLET, LlZA MACROLEPIS - Easterson, D C V; Kandasami, D; Paulraj, R (Indian Journal of Fisheries, 2011)
Seven feeds having 40% fat free protein from each one of the sources viz.coconut kernel oil cake, sesameseed oil cake, ground-nut oil cake, horse-gram, field-bean, bengal-gram and casein fortified withphenylalanine, argenine and cystine were formulated. Casein was taken as the standard protein.Carbohydrate content was kept at not less than 35% while lipid (Cod liver oil) content was maintained’at 5% vitamin mixture and mineral mixture (USP XIV) were at 2% level and Lambda varieties at 5% levelwas used as the binder. After feeding Liza macrolepis of 1.8 to 3.8 g (live weight with the experimentaldiets once a day for 15 days to satation, the performance of the diets towards eight conversion indiceswere ranked. The ranking of the vegetable proteins in the descending order of performance is as follows:coconut, ’bengal-gram, ground-nut, field-bean, sesame seed and horse-gram.